Korelasi ukuran badan, volume ambing dan produksi susu kambing Peranakan Etawah (PE) di Kecamatan Turi Kabupaten Sleman Yogyakarta - Dwi Nurul Febriana; Diah Wahyu Harjanti; Priyo Sambodho (Faculty of Animal Science, Universitas Brawijaya, 2018)
The outer performance can be used for livestock selection. Body size and udder can be used to assess livestock productivity. This study aimed to determine the correlation between body size (body length, shoulder height and chest size), udder volume and milk production. The material used were 35 lactation PE goats in the lactation period of II-III and lactation month of 4-5. The analysis used was simple linear correlation regression and non-linear quadratic. The results showed that milk production and udder volume did not increase during the increasing of body length. Shoulder height with udder volume and milk production have unreal correlation. The overall calculation shows that there is no relationship between chest size, udder volume and milk production in livestock. The udder volume with milk production shows a strong correlation. In conclusion, there is no relationship between body length, shoulder height and chest size with udder volume and milk production. The correlation between udder volume and milk production is more udder volume, more milk can be produced.